If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(8v + -3) = -8v + 36 Reorder the terms: -4(-3 + 8v) = -8v + 36 (-3 * -4 + 8v * -4) = -8v + 36 (12 + -32v) = -8v + 36 Reorder the terms: 12 + -32v = 36 + -8v Solving 12 + -32v = 36 + -8v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '8v' to each side of the equation. 12 + -32v + 8v = 36 + -8v + 8v Combine like terms: -32v + 8v = -24v 12 + -24v = 36 + -8v + 8v Combine like terms: -8v + 8v = 0 12 + -24v = 36 + 0 12 + -24v = 36 Add '-12' to each side of the equation. 12 + -12 + -24v = 36 + -12 Combine like terms: 12 + -12 = 0 0 + -24v = 36 + -12 -24v = 36 + -12 Combine like terms: 36 + -12 = 24 -24v = 24 Divide each side by '-24'. v = -1 Simplifying v = -1
| -13=5x+2 | | x^2-6xy+y^2=6 | | 3x+x+21=-7 | | 3x=-159 | | 4x-7=271 | | x+45+45+35=360 | | 5(x-1)=3x+25 | | 11x+16=93 | | 344/2 | | 5sin(x-5)/4cos(x-5) | | 7x+1=61 | | -5(7+n)=-37-4n | | 4+4x=21x+12 | | (2x+1)sq-6=19 | | 4+49x=21x+12x | | 11x+9=11x-6 | | -11f=7(-1-2f)+5 | | 7x*9-2=5x-6 | | 9h+3=7h+5 | | 300+10x=y | | 4/7=21/(x-3) | | 10n=9n-9 | | x-0.7x=44 | | -4m=-8-5m | | 15(t-6)+3t=6(3t+4)-8 | | 4x+26+3x+14=180 | | 4x+5=1x-10 | | 2s+4=5(-4+2s) | | 3j/5-8J | | 5x-10=-2(x+3)-11 | | 7x+3=-2y+3 | | 2(2x-5)(6x+11)=0 |